2023
DOI: 10.3390/jof9030298
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multi-locus Genotypes Detected in Aspergillus fumigatus Isolated from COVID Associated Pulmonary Aspergillosis (CAPA) and from Other Clinical and Environmental Sources

Abstract: Background: Aspergillus fumigatus is a saprophytic fungus, ubiquitous in the environment and responsible for causing infections, some of them severe invasive infections. The high morbidity and mortality, together with the increasing burden of triazole-resistant isolates and the emergence of new risk groups, namely COVID-19 patients, have raised a crescent awareness of the need to better comprehend the dynamics of this fungus. The understanding of the epidemiology of this fungus, especially of CAPA isolates, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This finding was replicated in one Spanish and one Portuguese study using tandem repeats within the exons of surface proteins and erg coding genes (TRESPERG), and microsatellite methods, respectively, to compare isolates obtained from CAPA patients and the environment [22,25]. The authors identified that the CAPA isolates were from a diverse genetic pool [22,23,25]. However, compared to WGS, TRESPERG and microsatellite methods are limited in their power to provide an in-depth analysis of the genetic structure and diversity within a population [57,58], due to only utilising a small proportion of the whole genome [58].…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…This finding was replicated in one Spanish and one Portuguese study using tandem repeats within the exons of surface proteins and erg coding genes (TRESPERG), and microsatellite methods, respectively, to compare isolates obtained from CAPA patients and the environment [22,25]. The authors identified that the CAPA isolates were from a diverse genetic pool [22,23,25]. However, compared to WGS, TRESPERG and microsatellite methods are limited in their power to provide an in-depth analysis of the genetic structure and diversity within a population [57,58], due to only utilising a small proportion of the whole genome [58].…”
Section: Discussionmentioning
confidence: 74%
“…A larger multicentre study using microsatellite methods to genotype isolates identified that the genotypes obtained were genetically distinct from one another [23]. This finding was replicated in one Spanish and one Portuguese study using tandem repeats within the exons of surface proteins and erg coding genes (TRESPERG), and microsatellite methods, respectively, to compare isolates obtained from CAPA patients and the environment [22,25]. The authors identified that the CAPA isolates were from a diverse genetic pool [22,23,25].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations